Two Atypical Cases of Hantavirus Infections from Sri Lanka. (19th April 2018) - Ehelepola, N. D. B.; Basnayake, B. M. L. S.; Sathkumara, S. M. B. Y.; Kaluphana, K. L. R.
Abstract : There are two categories of hantaviruses resulting in two distinct illnesses. The Old World (Asia and Europe) viruses give rise to hemorrhagic fever with renal syndrome (HFRS), and the New World (Americas) viruses cause hantavirus pulmonary syndrome (HPS). Hantavirus infections have very similar clinical pictures and epidemiology to leptospirosis. Here, we present two cases of hantavirus infections from Sri Lanka (in South Asia) initially misdiagnosed as leptospirosis and later further investigated and diagnosed as hantavirus infections with serological confirmation of the diagnosis. They had clinical pictures of a combination of both HFRS and HPS as well as the involvement of the central nervous system. Hantavirus infections are rarely diagnosed in South Asia. Reports on such atypical clinical pictures of hantavirus infections are extremely rare. Having arrived at the correct diagnosis late/retrospectively, both these patients recovered notwithstanding being seriously ill, indicating adequate supportive therapy can save lives in such cases. The emergence of the hantavirus, an infection seriously affecting multiple organ systems with a high case fatality rate that is spread by aerosol and other routes, could become a serious public health issue in Sri Lanka.